2015
DOI: 10.1371/journal.pone.0139565
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Omega-3 Fatty Acid Supplementation on Glucose Control and Lipid Levels in Type 2 Diabetes: A Meta-Analysis

Abstract: BackgroundMany studies assessed the impact of marine omega-3 fatty acids on glycemic homeostasis and lipid profiles in patients with type 2 diabetes (T2DM), but reported controversial results. Our goal was to systematically evaluate the effects of omega-3 on glucose control and lipid levels.MethodsMedline, Pubmed, Cochrane Library, Embase, the National Research Register, and SIGLE were searched to identify eligible randomized clinical trials (RCTs). Extracted data from RCTs were analyzed using STATA 11.0 stati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
77
2
8

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(97 citation statements)
references
References 42 publications
10
77
2
8
Order By: Relevance
“…Statins are generally first line therapy due to their ability to reduce cardiovascular morbidity and mortality in primary and secondary prevention and ezetimibe can be used in statin-intolerant individuals or as add on therapy (23, 24). For patients with isolated hypertriglyceridaemia, omega 3 fatty acid supplementation has been shown to be effective as shown in a meta-analysis including 20 randomized controlled studies ( n = 1,209 participants) that demonstrated individuals on supplements had triglyceride levels significantly decreased compared to controls (25). Fenofibrates and omega 3 fatty acid supplementation can be used alone or in combination, however care must be taken with fenofibrates if on statin therapy due to increased risk of skeletal toxicity (23, 24).…”
Section: Discussionmentioning
confidence: 99%
“…Statins are generally first line therapy due to their ability to reduce cardiovascular morbidity and mortality in primary and secondary prevention and ezetimibe can be used in statin-intolerant individuals or as add on therapy (23, 24). For patients with isolated hypertriglyceridaemia, omega 3 fatty acid supplementation has been shown to be effective as shown in a meta-analysis including 20 randomized controlled studies ( n = 1,209 participants) that demonstrated individuals on supplements had triglyceride levels significantly decreased compared to controls (25). Fenofibrates and omega 3 fatty acid supplementation can be used alone or in combination, however care must be taken with fenofibrates if on statin therapy due to increased risk of skeletal toxicity (23, 24).…”
Section: Discussionmentioning
confidence: 99%
“…A common comparison is that between studies undertaken in Asian countries vs. non-Asian ones. It has been reported that Asians showed a more marked decrease in the levels of TAGs in response to ϖ-3 fatty acids supplementation as compared to subjects within a USA/European group but, no significant differences were found for total cholesterol or BMI [157]. Flavonols have also been shown to significantly reduce TAGs, total and LDL-cholesterol in studies conducted in Asian countries as compared to those in the EU/European subgroup [7].…”
Section: Discussionmentioning
confidence: 99%
“…However, it should be noted that this is not a fully consistent finding, with the heterogeneity in responsiveness as yet not fully understood (9,10) . Consumption of EPA and DHA has also been shown to be associated with many other diseases, for example, autoimmune diseases such as rheumatoid arthritis, cancer, diabetes, respiratory diseases, gastrointestinal diseases, Alzheimer's disease, depression, as well as psychotic disorders, for example schizophrenia (11)(12)(13)(14) . The current recommended intakes for EPA plus DHA in the UK are ⩾450 mg/d (15) .…”
mentioning
confidence: 99%